2011
DOI: 10.3945/ajcn.110.007377
|View full text |Cite
|
Sign up to set email alerts
|

n–3 PUFAs in cancer, surgery, and critical care: a systematic review on clinical effects, incorporation, and washout of oral or enteral compared with parenteral supplementation

Abstract: This review shows the beneficial effects of n-3 FA supplementation in cancer, surgical oncology, and critical care patients. Supplementation in these specific patient populations could be considered with the route of administration taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 69 publications
(257 reference statements)
1
26
0
3
Order By: Relevance
“…After Omegaven ® infusions, the concentrations of EPA in plasma and WBC increased, and the AA/EPA ratio in plasma and WBC phospholipids decreased. The increase of EPA in plasma PL in this patient (around 2%) was comparable with the increase resulting in immune-modulation in earlier studies [30], but was lower than the increase reached in other studies in cancer patients [20,31]. In patient 2, monocytes were isolated to explore the incorporation and washout of n-3 PUFA from these cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…After Omegaven ® infusions, the concentrations of EPA in plasma and WBC increased, and the AA/EPA ratio in plasma and WBC phospholipids decreased. The increase of EPA in plasma PL in this patient (around 2%) was comparable with the increase resulting in immune-modulation in earlier studies [30], but was lower than the increase reached in other studies in cancer patients [20,31]. In patient 2, monocytes were isolated to explore the incorporation and washout of n-3 PUFA from these cells.…”
Section: Discussionsupporting
confidence: 77%
“…The incorporation in cancer patients after enteral supplementation was thought to be at least 3 to 4 weeks [19,32], but an increasing number of studies show the incorporation to occur within a day [30,33,34]. Depending on the frequency of blood sampling, incorporation within one or more days was also demonstrated after parenteral supplementation of n-3 PUFA in patients with sepsis and around surgery [31]. We took blood samples 2 days after the first infusion of Omegaven ® , and found incorporation of n-3 PUFA in WBC and plasma phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic and experimental data have suggested that consumption of fish oil (FO) rich in u-3 polyunsaturated fatty acids (PUFAs) may play a role not only in cancer prevention but also in cancer therapy [1,2]. Although different mechanisms of action have been discussed in the literature [3], the anticancer properties of u-3 PUFAs have been primarily ascribed to their ability to downregulate proinflammatory eicosanoid synthesis from cyclooxygenase-2 (COX-2) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Three recent systematic reviews outlined the effects of the supplementation of n-3 PUFA and two of them focused on parenteral supplementation (87)(88)(89) .…”
Section: N-3 Pufamentioning
confidence: 99%